Sequence diversity of the leukotoxin (lktA) gene in caprine and ovine strains of Mannheimia haemolytica. (20th April 2013) - Vougidou, C.; Sandalakis, V.; Psaroulaki, A.; Petridou, E.; Ekateriniadou, L.
Abstract : Mannheimia haemolytica is the aetiological agent of pneumonic pasteurellosis in small ruminants. The primary virulence factor of the bacterium is a leukotoxin (LktA), which induces apoptosis in susceptible cells via mitochondrial targeting. It has been previously shown that certain lktA alleles are associated either with cattle or sheep. The objective of the present study was to investigate lktA sequence variation among ovine and caprine M haemolytica strains isolated from pneumonic lungs, revealing any potential adaptation for the caprine host, for which there is no available data. Furthermore, we investigated amino acid variation in the N‐terminal part of the sequences and its effect on targeting mitochondria. Data analysis showed that the prevalent caprine genotype differed at a single non‐synonymous site from a previously described uncommon bovine allele, whereas the ovine sequences represented new, distinct alleles. N‐terminal sequence differences did not affect the mitochondrial targeting ability of the isolates; interestingly enough in one case, mitochondrial matrix targeting was indicated rather than membrane association, suggesting an alternative LktA trafficking pattern.